A Young Man with Sudden Headache and Vision Loss - Ahmad Tirmizi, Jobli; Sharifah Aishah, Wan Mohamad Akbar; Teh, Cheng Lay; Cheong, Yaw Kiet; Chuah, Seow Lin (MRE Press, 2023)
Introduction: The cerebrovascular adverse effects of methamphetamine include ischemic strokes, intracerebral haemorrhages and subarachnoid haemorrhages. There are few reports of methamphetamine-induced cerebral venous sinus thrombosis.